Effects of thermodynamic pressure on laminar spray flame propagation into monodisperse fuel droplet-mists - Ozel-Erol, Gulcan; Kucuk, Merve; Chakraborty, Nilanjan (Elsevier, 2025)
The effects of droplet diameter, overall equivalence ratio (0.8-1.5), and primary evaporation zone length (2-10 mm) on the burning velocity and thermal flame thickness in laminar n-heptane monodisperse spray flames under varying pressures (1.0-2.0 bar) have been analysed using 1D numerical simulations. It is observed that for gaseous premixed flames, both flame speed and thickness decrease with increasing pressure. However, in spray flames, flame thickness increases while burning velocity decreases as pressure rises, primarily due to reduced evaporation rates that limit fuel vapor availability. Larger droplet sizes further diminish evaporation rates, which lowers burning velocity and increases flame thickness, regardless of pressure. The finite evaporation rate also results in local equivalence ratios that are lower than the overall equivalence ratio in the heat release zone within the flame, especially at high pressures and with large droplets. In overall fuel-rich mixtures (e.g., for an overall equivalence ratio of 1.5), this can lead to more reactive gaseous mixtures and higher burning velocities than corresponding gaseous premixed flames, particularly for small droplets. Notably, the burning velocity in some spray flames can exceed the burning velocity of the corresponding premixed flames at the same gaseous-phase equivalence ratio at the heat release rate location. Enhanced burning velocity is also attributed to the generation of reactive species (e.g., H-2, C2H2, C2H4) from droplet evaporation and pyrolysis behind the flame front, which diffuse back into the reaction zone and accelerate the combustion process. However, the formation of these species diminishes at higher pressures, reducing this enhancement effect.
Keywords: Sprays; Premixed flame; Thermodynamic pressure; Droplet diameter; Equivalence ratio; Burning velocity; Flame thickness